2009
DOI: 10.1128/mcb.00998-08
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Receptor 3 Associates with and Tyrosine Phosphorylates p90 RSK2, Leading to RSK2 Activation That Mediates Hematopoietic Transformation

Abstract: Dysregulation of the receptor tyrosine kinase fibroblast growth factor receptor 3 (FGFR3) plays a pathogenic role in a number of human hematopoietic malignancies and solid tumors. These include t(4;14) multiple myeloma associated with ectopic expression of FGFR3 and t(4;12)(p16;p13) acute myeloid leukemia associated with expression of a constitutively activated fusion tyrosine kinase, TEL-FGFR3. We recently reported that FGFR3 directly tyrosine phosphorylates RSK2 at Y529, which consequently regulates RSK2 act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 33 publications
1
38
2
Order By: Relevance
“…We found that RSK inhibition demonstrated specific/increased toxicity to breast TICs when compared with normal hematopoietic stem cells. This is in line with a study by Kang et al, which showed that loss of RSK2 via knockout also had no affect on the hematopoietic stem cell subpopulation [44]. Collectively, these data indicate that RSK inhibition is effective at eliminating breast cancer TICs but unlike conventional chemotherapies has little effect on normal stem cells.…”
Section: Discussionsupporting
confidence: 80%
“…We found that RSK inhibition demonstrated specific/increased toxicity to breast TICs when compared with normal hematopoietic stem cells. This is in line with a study by Kang et al, which showed that loss of RSK2 via knockout also had no affect on the hematopoietic stem cell subpopulation [44]. Collectively, these data indicate that RSK inhibition is effective at eliminating breast cancer TICs but unlike conventional chemotherapies has little effect on normal stem cells.…”
Section: Discussionsupporting
confidence: 80%
“…21 In addition, it has recently been shown that FGFR3, by interacting with, and phosphorylating two tyrosine residues within the C-terminal region of RSK2, influences RSK2 activation. 23 Altogether, the data provide evidence that RSKs have an important role in cell-cycle progression, differentiation, and cell survival. 21 In the cytosol, RSK proteins have been shown to phosphorylate many substrates, including GSK3, L1CAM, the Ras GEF-Sos, IkB, the p34cdc2-inhibitory kinase Myt1, the translation factors eEF2, eIF4B, and the pro-apoptotic protein BAD (Figure 2).…”
Section: Rsk2 Protein Functionmentioning
confidence: 88%
“…9 TEL-FGFR3 is a constitutively activated fusion tyrosine kinase that is associated with t(4;12)(p16;p13) AML. 43 Genetic deficiency of RSK2 resulted in a significantly delayed and attenuated myeloproliferative syndrome induced by TEL-FGFR3 compared with wild type cells, suggesting that RSK2 may be required in TEL-FGFR3-induced pathogenesis and disease progression, but not lineage determination in hematopoietic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…16,30 We recently found that oncogenic FGFR3 phosphorylates and activates RSK2 to induce hematopoietic transformation. 7,9 Targeting RSK2 but not RSK1 by siRNA or treatment with a specific RSK inhibitor fmk 31,32 effectively induced apoptosis in FGFR3-expressing human t(4;14)-positive myeloma cells and primary patient myeloma cells. These findings suggest a critical role for RSK2 in FGFR3-induced hematopoietic transformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation